A case report of sepsis and death caused by Parvimonas micra, a rare anaerobe - Jiang, Yuhang; Qin, Weichao; Li, Jian; Gao, Yuan; Zeng, Yan (Frontiers in Public Health, 2022)
Parvimonas micra is a type of Gram-positive anaerobic cocci widely distributed in the oral cavity, gastrointestinal tract, respiratory tract, and female reproductive system mucosa. It is a conditional pathogen that can cause infections in the human oral cavity, wounds, and other areas as well as sepsis. In this case report, the patient's immune system was compromised by various underlying diseases and a pulmonary infection, which led to the entry of P. micra infection into the bloodstream. P. micra is a slow-growing organism (When a bloodstream infection occurs, flagging an anaerobic bottle of blood culture as positive will usually take >48 h), which makes it hard to secure timely blood culture results. Our patient's poor physical condition eventually led to sepsis, and she died after 5 days in the hospital.